Multitasking scheduling with alternate periods - Huo, Yujia; Miao, Cuixia; Kong, Fanyu; Zhang, Yuzhong (Journal of combinatorial optimization, 2023)
In this paper, we consider the multitasking scheduling with alternate odd-period and even-period. For the minimization of makespan on one single machine, we present a 2-approximation algorithm for the general case and a 4 3 -approximation algorithm for a special case when jobs have identical release dates. And we prove that the problem is strongly NP-hard when jobs have different release dates. For the minimization of makespan on identical parallel machines, we present a ( 5 2 - 1 m ) -approximation algorithm for the general case and a pseudo-polynomial time algorithm when the number of machines is constant. Furthermore, we prove that the single-machine scheduling of minimizing the lateness is strongly NP-hard.